Tinjauan Yuridis Terhadap Penyelesaian Perkara Wanprestasi Dalam Perjanjian Utang Piutang (Studi Kasus Pengadilan Negeri Surakarta) - Saifuddin, Amarullah; , Nuswardhani, S.H., S.U; , Darsono, S.H., MH (2015)
Loans is an agreement between one party to another and usually the common agreement is money. One party as the provider of the loan (creditor), while the other party is the party that receives the loan money (debtor). The essence of loans agreement is the creditors lend some money to the debtor, and the debtor shall repay it within a specified time along with interest. Loan repayment is redeemed by monthly installment. Oftenly, the repayment of the debtor is not as what it was agreed. If the debtor does not do what he was promised, it can be said he is breaching the loan agreement. This research uses descriptive normative method. Using secondary data and primary data. Literature studies, field studies and interviews are used as the techniques to collect the data. And with qualitative data analysis method. Based on the results of research and discussion the conclusion is that the breach of loans agreement which is done by debtor against the loans agreement inflicting some legal consequences/legal responsibilities/legal sanctions should be given, such as: debtor is obliged to pay the monetary loss suffered by the creditor or so called restitution, cancellation agreement, risk transition, debtor is obliged to pay the court costs if the case is filed upon trials, and the debtor is proven breaching the agreement. In the contex of restitution, these are included: fees or costs which have incurred, the actual monetary loss because of damage, the loss of the creditor's object caused by the negligence of the debtor, interests or provit which was expected.